2001
DOI: 10.1243/0957650011538703
|View full text |Cite
|
Sign up to set email alerts
|

Flow characteristics in the liner of a reverse-flow gas turbine combustor

Abstract: Investigation carried out in a plane model of a reverse-flow gas turbine combustor under isothermal flow conditions has shown that the bulk of the flow remains close to the outer liner wall between the rows of primary and dilution holes, while it shifts towards the liner mid-plane after the row of dilution holes. At the combustor outlet, the bulk of the flow remains towards the inner wall of the outlet duct, with a uniform flow distribution. At the outlet of the combustor model, turbulence intensity was approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Moreover, a comparison of experimental data with the results of a numerical computation demonstrates the capability of predicting the flow field in combustor diffusers with reasonable accuracy. Bharani et al [14] investigated the effect of swirl with different intensities at inlet on the flow characteristics in the outer annulus of a prototype reverse-flow gas turbine combustor. They observed that imposition of swirl improves the flow uniformity at outlet.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a comparison of experimental data with the results of a numerical computation demonstrates the capability of predicting the flow field in combustor diffusers with reasonable accuracy. Bharani et al [14] investigated the effect of swirl with different intensities at inlet on the flow characteristics in the outer annulus of a prototype reverse-flow gas turbine combustor. They observed that imposition of swirl improves the flow uniformity at outlet.…”
Section: Introductionmentioning
confidence: 99%
“…The outer liner surface has one row of plunged dilution holes and one row of plain primary Fig. 1 Schematic layout of the prototype combustor [7] Table 1 Geometric details of the prototype combustor Height of the inlet passage plane-A 12 mm Height of the outer annulus 8.5 mm Height of the inner annulus at the dome end 7.5 mm Height of the inner annulus at the turn-section 10.5 mm Diameter of dilution holes 7 mm Diameter of primary holes 3.5 mm Pitch of dilution holes 28 mm Pitch of primary holes 14 mm Swirl number 0.875 Protrusion of dilution holes tip surface 1.5 mm holes. The inner liner surface also has a similar type of dilution and primary holes placed just below the corresponding row of outer dilution and primary holes, such that the dilution and primary holes in the outer and the inner liner surface have the same axis.…”
Section: Geometry and Boundary Conditionsmentioning
confidence: 99%
“…Crocker and Smith [6] have predicted dilution zone flow behaviour for angular dilution jets. Bharani et al [7] investigated experimentally the flow characteristics in the liner of a reverse-flow combustor under isothermal flow conditions. Gordon and Levy [8] presented a numerical simulation to predict the reliability of CFD modelling in gas turbine combustors with complex geometry by modelling the entire flow field from the compressor diffuser to the turbine inlet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation